The therapeutic potential of bacterial lysates: applications and future perspectives - Diana Mihaela Alexandru; Diana Larisa Ancuţa (Medicamentul Veterinar)
The use of bacterial lysates in therapy has gained momentum due to their ability to modulate host immune responses. These preparations, derived from bacterial cell lysis, contain antigenic components that stimulate both innate and adaptive immunity. Despite their clinical applications in infectious, allergic, and oncological pathologies, the molecular mechanisms underlying their efficacy remain underexplored. This article reviews the current understanding of bacterial lysates, focusing on their therapeutic applications and future research directions.